Renal cell oncocytoma tumor evolutions: a case report - Alduraibi, Alaa Khalid; Essa, Noora Bin; Bomanji, Jamshed (Frontiers in Oncology, 2024)
This report delineates the clinical progression of a renal oncocytoma in a 38-year-old female, initially asymptomatic, over a three-year follow-up period following her treatment for papillary thyroid cancer. The timeline of this case is as follows: In 2016, the patient was treated with total thyroidectomy and I131 for thyroid cancer. During an annual follow-up, an incidental renal mass was detected via FDG PET/CT, initially characterized as a benign, non-FDG-avid renal oncocytoma. Over two years, this lesion demonstrated a remarkable increase in FDG uptake and a slight growth in size, coupled with new I131 uptake in subsequent scans. These findings led to a reassessment of the diagnosis, initially suggesting a potential small renal cell carcinoma (RCC). Histopathological analysis eventually confirmed the diagnosis of oncocytoma. This case is notable for the tumor's unusual metabolic evolution and the challenges it posed in differential diagnosis.